THE PRESENCE OF PLASTICS IN MARINE MAMMALS: COMMON TYPE MICROPLASTICS AND THEIR FEATURES - De la Cruz Marín, Isaí; Pérez García, Berenice; Núñez Nogueira, Gabriel; Cruz Ascencio, Mórvila (Kuxulkab', 2022)
The presence of microplastics in the aquatic environment encourages fauna to acquire these materials directly or indirectly through food, mainly. Marine mammals are no exception and due to their large size, they are susceptible to acquiring microplastics. This study seeks to define what type of polymers are present in aquatic mammals and what body distribution they have based on their properties, such as color, morphology, size, and type of polymer reported in the last four years and seven months. It was observed that compounds such as polypropylene, polyethylene terephthalate, and polyethylene are present in most marine mammals. The dominant colors of these microplastics become black, blue, colorless, green, and gray, among others. Based on morphology, fibers and fragments dominate in a size range that varies between 100-20,000 µm for fibers and 44-40,000 µm for fragments, respectively.
Keywords: Microplastics; Marine mammals; Gastrointestinal tract; Scats; Fibers